Factors related to students' satisfaction with holding e-learning during the Covid-19 pandemic based on the dimensions of e-learning. Issue 7 (July 2021) - Yekefallah, Leili; Namdar, Peyman; Panahi, Rahman; Dehghankar, Leila
Abstract: Background: E-learners' satisfaction has a significant impact on the success of the e-learning process and leads to improving the quality of the e-learning system. Many factors affect e-learning satisfaction. This study aimed to determine the factors related to students' satisfaction with e-learning during the Covid-19 pandemic based on the dimensions of e-learning. Methods: The present study was a cross-sectional study, which was conducted in 2020 among students studying in different fields of Qazvin University of Medical Sciences using stratified random sampling. To collect data three parts of questionnaires were used included the demographic information, the measuring the effectiveness of e-learning, and measuring the level of satisfaction with holding e-learning during the Covid-19 period. Data were entered into spss23 and analyzed by descriptive method, chi-square, and t-test. Results: The results showed that the mean (standard deviation) score of satisfaction with e-learning in the students was 20.75 (2.13) and 59 % of them had undesirable satisfaction. There was a significant relationship between satisfaction with e-learning and variables of gender and history of attending online classes before Covid-19. Regarding the four aspects of e-learning, there was a statistically significant difference between the two groups of students with desirable satisfaction and undesirable satisfaction. The results revealed that the mean scores of dimensions of teaching and learning; feedback and evaluation; flexibility and appropriateness; and workload among students with desirable satisfaction were higher than students with undesirable satisfaction. Conclusion: Considering the results, efforts should be made to improve the quality of e-learning and the factors affecting it, because due to the prevalence of Covid-19, distance education may be held for a long time. Lack of attention to these cases can reduce the quality of education and students' level of knowledge. Abstract : Satisfaction; e-learning; Covid-19.